Molecular mechanisms of TGFβ-mediated EMT of retinal pigment epithelium in subretinal fibrosis of age-related macular degeneration - Higashijima, Fumiaki; Hasegawa, Mina; Yoshimoto, Takuya; Kobayashi, Yuka; Wakuta, Makiko; Kimura, Kazuhiro (Frontiers in Ophthalmology, 2023)
Age-related macular degeneration (AMD) is one of the leading causes of blindness in the elderly, affecting the macula of the retina and resulting in vision loss. There are two types of AMD, wet and dry, both of which cause visual impairment. Wet AMD is called neovascular AMD (nAMD) and is characterized by the formation of choroidal neovascular vessels (CNVs) in the macula. nAMD can be treated with intravitreal injections of vascular endothelial growth factor (VEGF) inhibitors, which help improve vision. However, approximately half the patients do not achieve satisfactory results. Subretinal fibrosis often develops late in nAMD, leading to irreversible photoreceptor degeneration and contributing to visual loss. Currently, no treatment exists for subretinal fibrosis, and the molecular mechanisms of fibrous tissue formation following neovascular lesions remain unclear. In this review, we describe the clinical features and molecular mechanisms of macular fibrosis secondary to nAMD. Myofibroblasts play an essential role in the development of fibrosis. This review summarizes the latest findings on the clinical features and cellular and molecular mechanisms of the pathogenesis of subretinal fibrosis in nAMD and discusses the potential therapeutic strategies to control subretinal fibrosis in the future.